WRITING THE SELF IN RURAL MALI - (:unkn) unknown (My University, 2013)
In a comparative perspective, literacy has been closely associated with techniques of the self and with the emergence of modern subjectivities. But what happens when literacy is developed without genres such as diary keeping being widespread? Scrutinizing grassroots practices, this article demonstrates that even people who are not confronted with established forms of self-writing engage with literacy in ways that bear an imprint of their lives and subjectivities. Drawing on an ethnographic study in one village in southern Mali, it sets a socio-historical background where writing practices arise primarily as responses to the pressure of rural management. Yet the local discourses on the value of writing are suffused with notions of privacy. The article focuses on the unstable but shared practice of keeping a notebook for farming as well personal notations. Through a detailed analysis of two notebooks, it advocates for a set of distinctions between the individual, the private and the self that helps disentangle the issue of writing and self. This leads to a contrasted view of the local engagements with literacy. The question of the crystallization of notebook keeping as a genre remains open.
Keywords: African Research